Cerebral venous thrombosis in a patient with acute postinfectious glomerulonephritis - Morkhandikar, S. (Indian J Nephrol, 2016)
Thrombosis of the cerebral venous sinuses (CVT) is described in nephrotic syndrome. A 13-year-old girl was admitted with acute post-infectious glomerulonephritis (APIGN). Subsequently she developed recurrent seizures with focal neurological deficits. On evaluation, she was found to have CVT. To the best of our knowledge, this is the first report of CVT in APIGN. Identifying this complication is imperative, as timely diagnosis and treatment could be lifesaving.